The Influence of Socio-Economic Factors in Compensation Assessment: Case Study in District Court - Degdo Suprayitno; Terianus L. Safkaur; Jackson Yumame; Hiskia C. M Sapioper; Sriyono Sriyono (Rechtsnormen: Journal of Law, 2024)
Background on the influence of socioeconomic factors in the assessment of damages is important as legal systems in many countries, including Indonesia, often consider various factors when determining the amount of fair compensation for victims in civil cases. Socioeconomic factors such as income, social status and employment can affect a person's ability to obtain adequate compensation after suffering a loss. This research aims to study how district courts use socioeconomic factors to make decisions on the assessment of damages. This involves finding and understanding what components are most influential in the decision-making process. The quantitative method involved in-depth interviews and data collection. It also involved obtaining information from judges, lawyers, and other relevant parties to learn more about the socio-economic components that influence the assessment of punitive damages. This research may find that socio-economic components such as income, occupation or social status have a significant influence on the assessment of damages by the district court. For example, although the losses suffered may be the same, victims with low incomes are likely to receive lower damages than victims with high incomes. This research leads to the conclusion that action is needed to improve fairness in the assessment of damages in the district courts. This can be achieved by raising awareness of the impact of socio-economic factors and ensuring that all parties under the law receive fair treatment.